2020
DOI: 10.1007/s10072-020-04545-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lockdown on the management of ischemic stroke: an Italian experience from a COVID hospital

Abstract: Objective To evaluate the impact of the lockdown measures, consequent to the outbreak of COVID-19 pandemic, on the quality of pre-hospital and in-hospital care of patients with acute ischemic stroke. Methods This is an observational cohort study. Data sources were the clinical reports of patients admitted during the first month of lockdown and discharged with a confirmed diagnosis of stroke or TIA. Data were collected in the interval ranging from March 11th to April 11th 2020. As controls, we evaluated the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 10 publications
6
63
2
Order By: Relevance
“…However, Schirmer et al and Montaner et al describe a significant increase in stroke onset time to arrival at the hospital during the COVID-19 period for a collaboration of 12 hospitals in 6 states in the USA and Seville in Spain, respectively [ 6 , 10 ]. This is similar to Frisullo et al, who reported a significant increase in the onset-to-door time in the early phase of the pandemic in Rome [ 13 ]. Such differences may reflect different policies in prioritisation of stroke transfer and/or differing strain on existing services due to high numbers of COVID-19 patients.…”
Section: Discussionsupporting
confidence: 89%
“…However, Schirmer et al and Montaner et al describe a significant increase in stroke onset time to arrival at the hospital during the COVID-19 period for a collaboration of 12 hospitals in 6 states in the USA and Seville in Spain, respectively [ 6 , 10 ]. This is similar to Frisullo et al, who reported a significant increase in the onset-to-door time in the early phase of the pandemic in Rome [ 13 ]. Such differences may reflect different policies in prioritisation of stroke transfer and/or differing strain on existing services due to high numbers of COVID-19 patients.…”
Section: Discussionsupporting
confidence: 89%
“…In line with previous studies, the volume of IVT markedly decreased during the COVID-19 period [3][4][5][7][8][9][10]. The main factor for limiting the use of IVT among patients treated with MT was time delay.…”
Section: Discussionsupporting
confidence: 88%
“…The main factor for limiting the use of IVT among patients treated with MT was time delay. The volume of MT remained stable between the two periods while previous studies have reported conflicting results [3][4][5][8][9][10]. The regional variability of the impact of COVID-19 on acute stroke care is illustrated by a German study which found a relevant effect on MT in a only one out of four centers [10].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…130 Moreover, the availability of acute reperfusion therapies, including both intravenous thrombolysis and mechanical thrombectomy has been limited, according to recent reports from North America and Europe. [71][72][73][74][75] When administered, treatment time metrics are prolonged, negatively impacting the effectiveness of the treatments. 131 The performance of the more time-consuming, multiparametric stroke neuroimaging techniques is reported to have also declined, which, in turn, impedes the recognition of eligible patients for acute reperfusion therapies.…”
Section: Impact Of Covid-19 Pandemic On Stroke Managementmentioning
confidence: 99%